Dietary counselling for cardiovascular disease prevention in primary care settings: Results from a German physician survey - Goerig, Tatiana; Mayer, Manfred; Bock, Christina; Diehl, Katharina; Hilger, Jennifer; Herr, Raphael M.; Schneider, Sven (Family Practice, 2014)
Background: Primary care physicians (PCPs) play an important role in the promotion of healthy dietary behaviour. However, little is known about the practice of and factors associated with the provision of dietary counselling in primary health care in Germany. Objectives: To explore the attitudes towards and factors associated with the routine provision of dietary counselling in Germany using data from the nationwide, representative sample of the Physician Survey on Cardiovascular Disease Prevention. Methods: A total of 4074 randomly selected PCPs (response rate: 33.9%) provided data on dietary counselling for prevention of cardiovascular disease (CVD) based on the 5 A's (Assess, Advise, Agree, Assist, Arrange), attitudes towards dietary counselling and patients' and practice characteristics. Results: While the majority of PCPs (86%) reported having high levels of competence in providing dietary advice, only 49% felt they had been successful in counselling their patients on nutrition. PCPs routinely asked (68%) and advised patients to change their dietary habits more frequently (77%) compared to other counselling techniques based on the 5 A's. Female physicians and those with a higher percentage of privately insured patients and patients at higher risk of CVD were more likely to use the 5 A's to routinely counsel their patients on nutrition. Conclusions: The data showed high levels of involvement by German PCPs in CVD prevention and dietary counselling. The rather low perceived success of dietary intervention and differences with respect to patients' health insurance status indicate a need to address both communication skills in medical training and appropriate reimbursement of preventive services. ©The Author 2014. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Cardiovascular diseases; Counselling; Health behaviour; Physicians; Prevention; Primary health care